Accounting Ethics in the Era of Globalization: A Betawi Cultural Perspective - Muhammad Aras Prabowo; Kafka Nafisah Maulidiyah; Habsyah Fitri Aryani (Innovation Business Management and Accounting Journal, 2025)
This research examines the interpretation and application of accounting ethics in the Betawi community amidst the influence of globalization. Using the literature review method, this study explores how Betawi cultural values such as honesty, integrity, and social responsibility influence local accounting practices. The findings show that despite the pressure to adopt international accounting standards such as IFRS and GAAP, Betawi accounting practitioners try to maintain a balance between global standards and their local cultural values. This research underscores the importance of understanding accounting ethics in the context of local culture to strengthen sustainable accounting practices in Indonesia.